Teknologi dan Destruktivitas Manusia - Muhamad Ilham Faozi; Thufail Dhiva Arga Nugraha (Jurnal Multidisiplin Madani, 2022)
The development of technology began in primitive times along with human civilization, starting from conventional technology and evolving into an all-digital and sophisticated technology. Technology is a set that helps daily human activities. Of course, this will also impact human behaviour and civilization because technology affects the human experience using technology. Technology is included in all lines as a symbol of the progress of civilization and has a positive impact. However, technology that is considered the progress of the times has a negative impact, namely the destruction of nature due to technological destruction, such as global warming, consumerism, addiction, depression, and FOMO, which become problems due to the use of technology. Technology will affect the experience so that it affects the individual human person. Therefore, a development centred on the human point of view has a bad impact because everything is measured from the human point of view. As a result, nature is damaged, and many plants, the environment, and animals die, many animals die. Technology becomes an instrument that leads humans to destruction and arrogance, and arbitrary actions become human nature. Behind the technology behind bringing benefits, some things must be paid for. So there is a need for a discourse on development change by looking at all aspects so that the location of the problem can be known. Overcome, it is necessary to have a discourse on the ethics of responsibility, namely by looking at the negative impact before it happens. So that the development paradigm can be reviewed and practically, individuals can think of undesirable things to avoid.